An Empirical Test of an Asymmetric Information Model of Strikes - Tracy, Joseph S. (Journal of Labor Economics, 1987)
Recent developments in the theory of strategic bargaining demonstrate how informational asymmetries can lead to prolonged and costly bargaining. These models can be applied to contract negotiations, yielding an economic theory of strikes. To date, however, few empirical tests of these models have been carried out. In this paper, a set of predictions concerning the incidence and unconditional duration of strikes is derived from a simple bargaining model in which the union is uncertain about the firm's future profitability. These predictions are then tested on a micro data set of major U.S. contract negotiations that took place from 1973 to 1977.